ANALISA PEMBAYARAN SECARA KONTRAKTUAL KONSULTAN PENGAWAS DINAS CIPTA KARYA DAN TATA KOTA SAMARINDA - ISNO, SUTR (KURVA S JURNAL MAHASISWA, 2014)
In implementing activities consultant work supervisors, determine the time for monitoring the quality of the work being dilaksanakanya or rights as a consultant. in such work should be accompanied by the maintenance contract and contractual administration that has disepakti by both parties that the power user .pihak budget (KPA) and the supervision consultant for billing or payment procedures for supervising consultants.In the payment system contractually supervision consultant services copyright works and town planning samarinda, does not allow the problems or obstacles in the payment of the consultant. And the factors that most influence on contractual payment service supervisor consultant copyrighted works and town planning samarinda.A method for searching a problem or obstacle payments contractually supervising consultant, conducted by wawan way to the office of copyright works and town planning samarinda, while the method of finding the factors that affect the payments contractually supervision consultant with methods questioner to a supervisory consultant there didinas copyright samarind works and urban planning.From these results we can conclude THAT factors - factors that most affect the contractual payments consultant supervisor is the official report of progress supervision, supervision work report, the minutes of the handover. the third payment of the item can not be missed.